MiR-122 Promotes the Development of Colon Cancer by Targeting ALDOA In Vitro. (27th September 2019) - Li, Hong; Zhang, Xinhua; Jin, Zhao; Yin, Tao; Duan, Chuanyi; Sun, Junwei; Xiong, Rui; Li, Zilin
Non-coding RNAs, originally considered junk gene products, have taken center stage in view of their significant involvement in a spectrum of biological processes during human development, thereby offering novel therapeutic targets for improvement of treatment options. Accumulating evidence has demonstrated non-coding RNA dysfunction across various human cancers. In particular, microRNAs have emerged as key regulatory molecules in cancer biology. MicroRNAs are noninvasive, readily accessible biomarkers that can be effectively applied for diagnosis and prognosis of different tumor types, including colon cancer. In this study, we reanalyzed the available data with bioinformatics tools to identify differentially expressed microRNAs in colon cancer cells. The top 3 upregulated microRNAs (miR-10, miR-199, and miR-122) in colon cancer cells were further validated in tissues of clinical patients via reverse transcription-quantitative polymerase chain reaction. Our results showed that miR-122 significantly promotes the proliferation and invasion ability of SW480 and SW620 cells through inhibition of Aldolase, Fructose-Bisphosphate A ( ALDOA ) expression. We further summarized recent advances in our understanding of the functional relevance of microRNAs in cancer development and discussed the possible implications of specific microRNAs in colon cancer. This study extends our knowledge of microRNA involvement in colon cancer biology and presents novel candidates for the development of attractive therapeutic strategies.